Lytic coelomocyte death is tuned by cleavage but not phosphorylation of MLKL in echinoderms. - Kaiyu Chen; Sikou Shen; Zhimeng Lv; Ming Guo; Yina Shao; Chenghua Li (PLoS Pathogens)
Lytic cell death including necroptosis and pyroptosis is induced by mixed lineage kinase domain-like protein (MLKL) phosphorylation and inflammatory caspase specific cleavage Gasdermins in higher mammals, respectively. In this study, we identified a novel MLKL homolog containing a tetrapeptide recognition motif (14-LVAD-17) of inflammatory caspase from Apostichopus japonicus,which was absent of Gasdermins member by genome screening. Functional analysis revealed that AjMLKL was involved in the regulation of Vibrio splendidus AJ01 infection induced lytic coelomocyte death in a cleavage-dependent manner, but not through RIPK3-dependent phosphorylation as mammals. Mechanistically, the activated form of cysteine-aspartic specific proteases-1 (AjCASP-1) bound to the tetrapeptide site of AjMLKL and cleaved it at Asp17. Cleaved AjMLKL18-491 displayed higher binding affinities towards phosphatidylinositol phosphate and cardiolipin compared to those of un-cleaved form. In addition, cleaved AjMLKL18-491 exerted stronger ability in disrupting the membrane integrity of liposome. More importantly, AjMLKL18-491 caused a large non-selective ionic coelomocyte pore and could directly kill the invasive AJ01. Moreover, activation of inflammatory AjCASP-1 was further found to be dependent on forming an inflammasome-like complex via CASc domain of AjCASP-1 and the N-terminal Ig domains of internalized AjNLRC4. All our results proved first evidence that lytic cell death was activated through MLKL cleavage, not MLKL phosphorylation in echinoderm, which offered insights into the functional, evolutionary mechanisms of lytic cell death in invertebrates.